2022
DOI: 10.1017/s095457942100153x
|View full text |Cite
|
Sign up to set email alerts
|

Vocalization and physiological hyperarousal in infant–caregiver dyads where the caregiver has elevated anxiety

Abstract: Co-regulation of physiological arousal within the caregiver–child dyad precedes later self-regulation within the individual. Despite the importance of unimpaired self-regulatory development for later adjustment outcomes, little is understood about how early co-regulatory processes can become dysregulated during early life. Aspects of caregiver behavior, such as patterns of anxious speech, may be one factor influencing infant arousal dysregulation. To address this, we made day-long, naturalistic biobehavioral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 86 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…But we have also discussed evidence that, in some situations, the opposite pattern can develop, giving rise to active dysregulation (metastatic processes) (Wass, 2023). As we describe in the context of ADHD, for example, increases in child arousal might be followed by an increase in child oppositional behaviour, followed by an increase in caregiver CNS arousal, followed by an increase in caregiver expressed emotions, followed by a further increase in child arousal, and so on (Granic & Patterson, 2006; Hollenstein et al., 2017; Lunkenheimer et al., 2017; Smith et al., 2023; Wass, 2023; see Figure 3C). Because they are hard to elicit and study in the laboratory, these types of child–caregiver interactions are under‐researched, both in the context of observational and intervention studies.…”
Section: Part 5—conclusionmentioning
confidence: 97%
See 3 more Smart Citations
“…But we have also discussed evidence that, in some situations, the opposite pattern can develop, giving rise to active dysregulation (metastatic processes) (Wass, 2023). As we describe in the context of ADHD, for example, increases in child arousal might be followed by an increase in child oppositional behaviour, followed by an increase in caregiver CNS arousal, followed by an increase in caregiver expressed emotions, followed by a further increase in child arousal, and so on (Granic & Patterson, 2006; Hollenstein et al., 2017; Lunkenheimer et al., 2017; Smith et al., 2023; Wass, 2023; see Figure 3C). Because they are hard to elicit and study in the laboratory, these types of child–caregiver interactions are under‐researched, both in the context of observational and intervention studies.…”
Section: Part 5—conclusionmentioning
confidence: 97%
“…prefrontal cortex), while the ERP literature points towards hyperreactivity to, and sustained processing of, neutral infant cues (Yatziv, Vancor, Bunderson, & Rutherford, 2021). Home studies have suggested that anxious caregivers tend to over‐respond to small‐scale physiological changes in their child (Smith et al., 2023), relative to depressed and control caregivers (Beebe et al., 2008; Granat, Gadassi, Gilboa‐Schechtman, & Feldman, 2017), and to show higher behavioural synchrony with their children during laboratory‐based interaction (Doba et al., 2022; Granat, Gadassi, Gilboa‐Schechtman, & Feldman, 2017; Lemus, Vogel, Greaves, & Brito, 2022). This is consistent with findings that higher levels of caregiver–child synchrony are observed in ‘high‐risk’ samples (e.g.…”
Section: Part 4—atypical Coregulatory Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational and embodied models can be used to test simple predictions about feedback loops between brain and environment, and targeted intervention studies can be employed to test causality. Although these and similar ideas have been discussed in the context of disorders such as ADHD and anxiety (Smith et al., 2021) they remain relatively under‐explored in the research literature (Wass, 2021).…”
Section: Early Activity Level In Adhdmentioning
confidence: 99%